Combination of Pyrosequencing® and Sanger sequencing reveals alleged novel mutation in exon 18 of EGFR. (March 2013) - Schildgen, Verena; Schulz, Carolin; Lüsebrink, Jessica; Tillmann, Ramona-Liza; Engel-Riedel, Walburga; Stoelben, Erich; Schildgen, Oliver; Brockmann, Michael
Background: EGFR sequencing is crucial for therapeutic decisions in treatment regimens of lung cancer patients. Several mutations have been identified in the past, of which some were confirmed as activating or resistance mutations by in vitro phenotyping. In this study, novel mutations of so far unknown relevance were identified by a combination of Sanger and Pyrosequencing ® .Materials & methods: Formalin-fixed paraffin-embedded lung biopsies from 20 randomly selected patients suffering from non-small-cell lung cancer with previous external EGFR mutation analyses were reanalyzed by Sanger sequencing according to a previous study, and Pyrosequencing with the EGFR Pyro Kit (Qiagen, Hilden, Germany). Sensitivity and specificity were determined in comparison with the results of an external supplier for all relevant mutations in exons 18, 19, 20 and 21.Results: Our analyses revealed that Pyrosequencing is faster and more sensitive for the common mutations compared with Sanger sequencing and the results of the external supplier. A new mutation, c.2160delC, in exon 18 in 40% of patients leading to a frameshift was identified. Another two frameshift mutations were detected in exon 18 in 10% of patients; c.2168delT in combination with c.2160delC, and c.2163insG alone.Conclusion: Divergences regarding the detection of the common mutations could be traced back to inhomogeneous or insufficient tumor material. Surprisingly, none of the newly identified mutations have been previously described, although they occurred in total in up to 40% of randomly selected cases. A possible explanation may be that commercial assays did not cover these deletions that are located nearby but not in the known mutation hotspot of exon 18, or that Sanger sequencing produced serious artifacts.